Effective Mechanisms of State-Legal Regulation in Higher Education: Analysis and Implementation Framework - Guzal Galiakbarova; Muslim Khassenov; Elmira Omarova; Svetlana Zharkenova; Zhamilya Berdiyarova; Sholpan Saimova (Emerging Science Journal, 2025)
This study analyzes how state-legal control has fostered higher education in Kazakhstan using the best legal techniques from the US, UK, Germany, and France. Kazakhstan needs strong legislative power, economic accountability, institutional independence, and academic freedom to develop its university system and compete globally. The study aims to establish a state-legal regulating structure for Kazakhstan's universities using global best practices. The study used panel data from 2000 to 2023 using the ARDL approach to assess the long-term and short-term effects of legislative and policy issues on higher education quality. The Pedroni residual cointegration test confirms long-run equilibrium relationships between variables, and robust least squares regression analyzes country-specific effects. The panel ARDL found that firm legal control, public education spending, research and development, and student mobility improve higher education quality. However, university autonomy has varied effects in the long run. Short-term academic independence hurts education quality, but student mobility is desirable. Results show that public education investment and student mobility increase higher education in Kazakhstan, but academic freedom diminishes it. US education quality is improved by strict legislative oversight but lowered by public education funding and university autonomy. This study developed the LEGAF-EDU (Legal, Governance, Autonomy, and Funding for Higher Education Development) Framework, a transformative model for Kazakhstan's regulatory concerns. This strategy combines legislative monitoring with institutional autonomy to create a stable, flexible government that assures high-quality education and holds the state accountable. The study advances legislation and policy by proposing an evidence-based higher education reform for Kazakhstan.